REPRESENTASI NILAI PENDIDIKAN KARAKTER DALAM SASTRA ANAK DIGITAL (REPRESENTATION OF CHARACTER EDUCATION VALUES IN DIGITAL CHILDREN'S LITERATURE) - Novitasari, Aulia; Cahaya, Noor; Huda, Nurul (Universitas Lambung Mangkurat, 2025)
AbstractRepresentation of Character Education Values in Digital Children’s Literature. This study aims to analyze the representation of character education values in five digital children's stories using Roland Barthes' semiotic approach. This study uses a qualitative approach with a content analysis method. The research data consists of texts from five digital children's stories on the Budi website. Qualitative content analysis was conducted by uncovering the meaning of denotation, connotation, and myth. The research data sources consist of digital children's stories with the theme of embracing children with special needs. The results show that each story contains the construction of character values relevant to character education, namely the values of caring, empathy, courage, tolerance, cooperation, and self-acceptance. The representation of character values is constructed through linguistic and narrative signs that produce social myths about inclusivity, family affection, and respect for diversity. The results of this study provide findings on the role of digital children's literature as a strategic medium in strengthening literacy and character education for child readers.Keywords: digital children's literature, character education, inclusivity, literacyAbstrakRepresentasi Nilai Pendidikan Karakter dalam Sastra Anak Digital. Penelitian ini bertujuan untuk menganalisis representasi nilai pendidikan karakter dalam lima cerita anak digital menggunakan pendekatan semiotika Roland Barthes. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi. Data penelitian berupa teks dari lima cerita anak digital di situs Budi. Analisis isi kualitatif dilakukan dengan mengungkap makna denotasi, konotasi, dan mitos. Sumber data penelitian terdiri dari cerita anak digital dengan tema perangkulan anak berkebutuhan khusus. Hasil penelitian menunjukkan bahwa setiap cerita memuat konstruksi nilai karakter yang relevan dengan pendidikan karakter takni nilai kepedulian, empati, keberanian, toleransi, kerja sama, dan penerimaan diri. Representasi nilai karakter dibangun melalui tanda-tanda linguistik dan naratif yang menghasilkan mitos sosial tentang inklusivitas, kasih sayang keluarga, dan penghargaan terhadap keberagaman. Hasil penelitian ini memberikan temuan terhadap peran sastra anak digital sebagai media strategis dalam penguatan literasi dan pendidikan karakter pembaca anak. Kata-kata kunci: representasi, pendidikan karakter, sastra anak digital, literasi